Description of two new species of the catfish genus Trichomycterus from southeastern Brazil (Siluriformes: Trichomycteridae) - Alencar, Aline R.; Costa, Wilson J.e.m. (Zootaxa, 2004)
Two new species of Trichomycterus from isolated small river basins of southeastern Brazil are described: T. pantherinus, new species, from the Rio Santa Maria da Vit ria basin, and T. caudofasciatus, new species, from the Rio Itabapoana basin. Both new species are diagnosed by a combination of morphological features, also occurring in T. alternatus and T. longibarbatus, including number of pectoral-fin rays, odontodes and branchiostegal rays, long filamentous first pectoral-fin ray and wide opercular patch of odontodes. Trichomycterus pantherinus differs from other congeners by possessing a light orangish yellow flank with dark brown to black rounded spots. Trichomycterus caudofasciatus is distinguished from other species of the genus by having four gray bars on the caudal fin.